1974
DOI: 10.1037/h0037211
|View full text |Cite
|
Sign up to set email alerts
|

Brightness discrimination of pretrained and nonpretrained hippocampal rats reinforced for choosing brighter or dimmer alternatives.

Abstract: Experimentally naive and pretrained hippocampeotomized, cortical control, and nonoperated rats were trained to choose either the brighter or dimmer arm of a Y-maze for water reinforcement. Nonpretrained hippocampectomized rats and to a lesser extent cortical control rats, initially preferred the dimmer arms of the maze. Nonpretrained hippocampectomized, cortical control, and nonoperated rats reinforced for entering the brighter arm did not differ, but when reinforced for entering the dimmer arm nonoperated sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
1

Year Published

1976
1976
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 28 publications
0
4
1
Order By: Relevance
“…Although hippocampal-Iesioned rats are clearly capable of solving sirnultaneous brightness discriminations (Bauer, 1974;Kimble, 1963;Silviera & Kimble, 1968;Winocur & Gilbert, 1984), in the present study, the hippocampal rats were unable to reacquire the black-white MTS task even when the sampie and comparison cues were present simultaneously. Nor were they able to acquire postoperatively a simultaneous nonmatching-to-sample (NMTS) version of this task.…”
Section: Discussioncontrasting
confidence: 70%
“…Although hippocampal-Iesioned rats are clearly capable of solving sirnultaneous brightness discriminations (Bauer, 1974;Kimble, 1963;Silviera & Kimble, 1968;Winocur & Gilbert, 1984), in the present study, the hippocampal rats were unable to reacquire the black-white MTS task even when the sampie and comparison cues were present simultaneously. Nor were they able to acquire postoperatively a simultaneous nonmatching-to-sample (NMTS) version of this task.…”
Section: Discussioncontrasting
confidence: 70%
“…In fact, animals with hippocampal lesions are often less .distractible on goal-directed tasks (Wicklegren & Isaacson, 1963). However, subsequent research has suggested that this might only apply to very salient stimuli, as animals show greater reactivity to unexpected events (orienting response), and poor attentional performance on discrimination tasks with low-intensity, low-salience stimuli (Bauer, 1974). Furthermore, the relationship of target to background stimuli greatly influences performance after hippocampal damage (Kaplan, 1968).…”
Section: The Hippocampusmentioning
confidence: 99%
“…Hippocampal lesions do not impair learning of easy visual discriminations (Bauer, 1974;Gazzara & Altman, 1981), because the visual-related regions can also mediate such learning. Hippocampal damage, on the other hand, impairs learn-ing of difficult discriminations (Bauer, 1974;Gazzara & Altman, 1981;Grieshach, et al, 1998), because the hippocampus may contribute more to learning difficult visual discrimination. Blocking NMDA receptors impairs certain forms of learning including olfactory discrimination learning (Morris et al 1986;Grieshach et al, 1998;Xu et al, 1995Xu et al, , 1998Xu et al, , 2003.…”
Section: Discrimination Learning and Brain Co Activitymentioning
confidence: 99%
“…Hippocampectomized rats learned difficult brightness discriminations significantly more slowly than controls, but showed no significant difference from control rats in easy brightness discriminations (Bauer, 1974). Rats with hippocampal microneuronal hypoplasia showed learning deficits in difficult visual discriminations, but not in easy discriminations (Gazzara & Altman, 1981).…”
mentioning
confidence: 97%
See 1 more Smart Citation